Oncological outcomes and complication rates after laparoscopic‐assisted cryoablation: a European Registry for Renal Cryoablation (EuRECA) multi‐institutional study. (26th August 2016) - Nielsen, Tommy K.; Lagerveld, Brunolf W.; Keeley, Francis; Lughezzani, Giovanni; Sriprasad, Seshadri; Barber, Neil J.; Hansen, Lars U.; Buffi, Nicole M.; Guazzoni, Giorgio; van der Zee, Johan A.; Ismail, Mohamed; Farrag, Khaled; et al.
Abstract : Objective: To assess complication rates and intermediate oncological outcomes of laparoscopic‐assisted cryoablation (LCA) in patients with small renal masses (SRMs). Patients and Methods: A retrospective review of 808 patients treated with LCA for T1a SRMs from 2005 to 2015 at eight European institutions. Complications were analysed according to the Clavien–Dindo classification. Kaplan–Meier analyses were used to estimate 5‐ and 10‐year disease‐free survival (DFS) and overall survival (OS). Results: The median [interquartile (IQR)] age was 67 (58–74) years. The median (IQR) tumour size was 25 (19–30) mm. The transperitoneal approach was used in 77.7% of the patients. The median postoperative hospital stay was 2 days. In all, 514 patients with a biopsy‐confirmed renal cell carcinoma (RCC) were available for survival analyses. The median (IQR) follow‐up for the RCC‐cohort was 36 (14–56) months. A total of 32 patients (6.2%) were diagnosed with treatment failure. The 5‐/10‐year DFS was 90.4%/80.0% and 5‐/10‐year OS was 83.2%/64.4%, respectively. A total of 134 postoperative complications (16.6%) were reported, with severe complications (grade ≥III) in 26 patients (3.2%). An American Society of Anesthesiologists score of 3 was associated with an increased risk of overall complications (odds ratio 2.85, 95% confidence interval 1.32–6.20; P = 0.005). Conclusions: This large series of LCA demonstrates satisfactory long‐term oncological outcomes for SRMs. However, although LCA is considered a minimally invasive procedure, risk of complications should be considered when counselling patients.